Analysis of flexural behavior of one-way reinforced concrete slab casted by shotcrete contain various types of plastic fibers - Jawhar, Abdulfatah; Mansoor, Yousif; Al-Hadithi, Abdulkader (Iraqi Journal of Civil Engineering, 2023)
The design of reinforced concrete structures has traditionally relied on empirical techniques based on experience or experimental research on actual structural members. Although this approach produces a high level of precision, it is usually exceedingly costly and time-consuming. This paper studied the convergence between theoretical analysis (ACI 318-19 Equations) and numerical analysis (FEM) of eleven one way reinforced concrete slab specimens casted by shotcrete contains three types of plastic fibers including waste plastic (PET), polypropylene (PP), and hybrid (PET+PP) fibers with three addition ratios (0.35%, 0.7%, and 1%) for each type. The results concluded that the numerical analysis (ANSYS FE model) showed a good agreement with the theoretical (ACI 318-19) of one-way slab in terms of ultimate load, with a variance, and standard deviation equal to 0.00076, and 0.027 respectively. Hence, ANSYS v15 software can be used for the analysis of reinforced concrete slabs casted by shotcrete contain waste plastic fibers and polypropylene fibers.